Ethnic issues in Paul's letter to the Romans changing self-definitions in earliest Roman Christianity - Walters, James C. (Valley Forge, PA Trinity, 1993)
Includes bibliographical references.
Keywords: Bible. N.T. Romans -- criticism, interpretation, etc; Jews -- Rome -- history; Jews in the New Testament; Rome -- ethnic relations -- history; Ethnicity -- Religious aspects -- Christianity -- history of doctrines -- early church, ca. 30-600.